PENINGKATAN PENGAWSAN PARTISIPATIF DALAM PENYELENGGARAAN PEMILIHAN KEPALA DAERAH - Rosidin, Utang (Jurnal Keadilan Pemilu, 2024)
The purpose of this article is to analyze the urgency of participatory supervision in the implementation of the 2024 regional head elections and the authority of Bawaslu in improving participatory supervision of the implementation of regional head elections. The method used in this study uses a normative legal approach. The results of the study show that the urgency of participatory supervision is an effort to ensure that each voter votes intelligently, which can be done by voters by collecting data, information and inventorying findings of alleged violations related to the implementation of regional head elections carried out by the community or independent organizations. Participatory supervision aims to realize the implementation of an honest, fair, clean and transparent election process and the results can be accepted by all parties, both election participants and the community. Bawaslu as the election organizer is responsible for the implementation of all stages of the implementation of quality, integrity and dignified regional head elections, which are expected to be able to encourage and continue to strengthen election supervision by providing reinforcement in the form of regulations, authority, human resources, and adequate facilities and infrastructure. The form of activity as one of the authorities owned by Bawaslu in increasing community participatory supervision in the process of organizing regional head elections is through Participatory Supervision Education (P2P) activities organized by Bawaslu Regency/City, given to various groups of people, especially new voters to optimize the understanding and desire of the community to increase participatory supervision carried out by the community. In addition to these activities, Bawaslu also continues to optimize efforts to increase participatory supervision carried out by the community, including through the formation of supervision villages in the community environment, socialization to community groups about the importance of supervision of the implementation of regional head elections which is packaged in various forms of activities.